18-month clinical evaluation of a copper-containing universal adhesive in non-carious cervical lesions: A double-blind, randomized controlled trial. (November 2019) - Matos, Thalita P.; Gutiérrez, Mario F.; Hanzen, Taise A.; Malaquias, Pâmela; de Paula, Alexandra M.; de Souza, Jullian J.; Hass, Viviane; Fernández, Eduardo; Reis, Alessandra; Loguercio, Alessandro D.
Abstract: Objective: This study aimed to evaluate the addition of copper nanoparticles (CuNp) on the clinical performance of a universal adhesive system used as etch-and-rinse (ER) and self-etch (SE). Methods: 216 restorations were randomly placed in 36 subjects according to the following groups: ER cu = etch-and-rinse with 0.1% CuNp; ER ct = etch-and-rinse without CuNp; SE cu = self-etch with 0.1% CuNp; SE ct = self-etch without CuNp. Resin composite was placed incrementally and light-cured. The restorations were evaluated at baseline and 6, 12 and 18 months using the FDI and USPHS criteria. Statistical analyses were performed using appropriate tests (α = 0.05). Results: The addition of CuNp did not increase the clinical performance (FDI / USPHS) of the universal adhesive tested after 18-month when applied in the ER mode (p > 0.05). The addition of CuNp in SE restorations increased the retention rate significantly and decreased the marginal discrepancies after 18 months (p < 0.05). Conclusion: The clinical performance of universal adhesive was significantly increased when applied in the SE mode with the addition of copper nanoparticles. Clinical relevance: This is the first study that demonstrates a slight improvement in the clinical performance of universal adhesive systems in non-carious cervical lesions when added CuNp in lower concentration.